Quantitative Detection of Pork Contamination in Cooked Meat Products by ELISA. (23rd November 2019) - Thienes, Cortlandt P; Masiri, Jongkit; Benoit, Lora A; Barrios-Lopez, Brianda; Samuel, Santosh A; Cox, David P; Dobritsa, Anatoly P; Nadala, Cesar; Samadpour, Mansour
Abstract: Recent news of many cases of adulteration of meats with pork has bolstered the need for a way to detect and quantify the unwanted contamination of pork in other meats. To address this need, Microbiologique, Inc. has produced a sandwich ELISA assay that can rapidly quantify the presence of pork in cooked horse, beef, chicken, goat, and lamb meats. We carried out a validation study and showed that this assay has an analytical sensitivity of 0.00014 and 0.00040% (w/v) for cooked and autoclaved pork, respectively, and an analytical range of quantitation of 0.05–3.2% (w/v) in the absence of other meats. The assay can measure pork contamination down to 0.1% (w/w) in the presence of cooked horse, beef, chicken, goat, and lamb meats. The assay is quick and can be completed in 1 h and 10 min.